Pembelajaran Geometri Berbasis Etnomatematika pada Peninggalan Perang Dunia II di Pulau Morotai - Akmal Hi. Dahlan; Alofrin Forno (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to facilitate students to develop mathematical thinking skills in expressing geometric elements contained in the World War II (WWII) museum in Morotai Island Regency. This research is a qualitative descriptive study that describes all student activities in the field (musium) to in the classroom, using the Group Investigation (GI) learning model approach. The results showed that ethnomathematics is good for learning in schools that are close to students' real lives. The results of this study also show that after applying ethnomathematical-based learning using the GI learning model, it can motivate and increase students' activeness and confidence in expressing opinions. From the results of this study, it is suggested, as teachers, they should create an innovative atmosphere that can develop talent, foster interest and educate students to develop mathematical thinking skills, so that the concept of learning mathematics obtained is expected to be better and collaborated with cultural problems so that mathematics is not too far away. from the real life of students, thus mathematics is not seen as a mere abstract science.